GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 116259 species occurrences available in GBIF matching the query: TaxonKey: Reptilia Laurenti, 1768 HasCoordinate: true HasGeospatialIssue: false Country: United Kingdom. The dataset includes 116259 records from 72 constituent datasets: 28 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 71 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 73 records from Norwich Reptile Study Group - Norwich Reptile Study Group Records for 2011. 673 records from Paleobiology Database. 994 records from Staffordshire Ecological Record - SER Species-based Surveys. 1635 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria . 14 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 13 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from University of Alberta Museums, Amphibian and Reptile Collection. 28 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 1724 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 2 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 292 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 3 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 3 records from National Trust - Ickworth species data held by The National Trust.. 35 records from iNaturalist research-grade observations. 13 records from MfN - Fossil plants (Mesophytic). 3 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 1 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 68371 records from Amphibian and Reptile Conservation - The ARC (formerly The HCT) Rare Species Database. 781 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups. . 11 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 7 records from MVZ Herp Collection (Arctos). 318 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 1 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from naturgucker. 2353 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 5479 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1655 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire REPTILE Records 1950-2007. 1 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 48 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 3 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 129 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 2 records from Countryside Council for Wales - Freshwater Site Visits. 1 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 1 records from Tartu University, palaeontology collections. 2 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 185 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 36 records from Norwich Reptile Study Group - Norwich Reptile Study Group Records for 2010. 1 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 4 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 56 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 35 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 1 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010) . 2822 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records . 14 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 39 records from University of California Museum of Paleontology. 1 records from CAS Herpetology (HERP). 20 records from National Trust - Hatfield Forest species data held by The National Trust.. 364 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 1174 records from Marine Environmental Monitoring - Marine Turtles. 8 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 260 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups. . 16229 records from Biological Records Centre - Reptiles and Amphibians Dataset. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 94 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 672 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 32 records from Seil Natural History Group - SNHG Biological Records Dataset. 1534 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 6 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 12 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 8 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 4 records from Tullie House Museum - Tullie House Museum Natural History Collections. . 1 records from Countryside Council for Wales - Amphibian & Reptile Licence Return Data . 12 records from National Trust - Heigham Holmes species data held by The National Trust. 7 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 4 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009.
Keywords: GBIF; biodiversity; species occurrences